Quality care management of febrile illnesses among children under 5 years in Atwima Kwanwoma district in the Ashanti Region of Ghana - Asante, Samuel Koranteng (2021)
A thesis submitted to the Department of Health Policy, Management, and Economics, School of Public Health, College of Health Sciences, Kwame Nkrumah University of Science and Technology, in partial fulfillment of the requirement for the award of the degree of Masters of Public Health, Health Services Planning and Management.